Comparación bromatológica, compuestos fenólicos y capacidad antioxidante de tres variedades de frejol caupí (Vigna unguiculata) de la Estación Experimental San Ramon – INIA - Gómez Reátegui, Valeria Marcela (2024)
The objective of this research was to evaluate the differences in nutritional and functional characteristics of three varieties of cowpea: black, brown, and white. Although cowpea is an important crop in Peru, its per capita consumption is relatively low compared to other countries. The study included a proximate analysis that revealed that all varieties are rich in protein (22.45% to 23.72%) and fiber (4.15% to 4.82%), with an energy content of approximately 345 to 349 kcal per 100 g. The color characteristics of the beans were evaluated using a colorimeter, showing that the black variety had a lower luminosity and higher values in the a* and b* coordinates, indicating a darker color. Total phenolic compounds were quantified using the Folin-Ciocalteu method, finding that the black variety had the highest content (38.15 ± 2.49 mg EAG/100 g DM). Antioxidant capacity was measured by DPPH and ABTS assays, where the black variety also showed the highest antioxidant activity. Principal Component Analysis (PCA) confirmed that differences in phenolic compound content and antioxidant capacity are significant among varieties. The research concludes that cowpeas, especially black-colored, represent a valuable source of nutrients and bioactive compounds, underlining the need to promote their consumption to improve public health and nutrition in Peru.